SUPRESSIVE SOIL BIOCONTROL MODEL BASED ON COMPARATIVE METAGENOMIC APPROACH OF SOIL AROUND HEALTHY AND Fusarium oxysporum INFECTED BANANAS (Musa acuminata L.) - Ahmad Herdiansyah, Sandy
Banana commodity (Musa acuminata L.) in Indonesia has a high level of market demand and its cultivation is carried out intensively on a large scale. A common problem in banana plantations is Fusarium oxysporum f. sp. cubense (Foc) which causes wilting of banana plants. Foc spores can be persistent in the soil over a long period time, causing banana plantations to be replaced by other commodities. One alternative to increasing banana resistance is to increase the level of soil suppression against Foc to reduce the incidence of plant infection by the disease through antagonistic interactions between microbes and pathogens. Need information about the composition of microbes in soils that are naturally suppressive as an effort to develop soil models that can control Foc infection. The development of high throughput sequencing technology helps the analysis of microbial composition as a whole, but the analysis requires a computational process that is not simple. Comparative metagenomic analysis using high throughput sequencing of 16S rRNA components was performed to compare the diversity and composition of microbes in soils between healthy bananas and Foc infected as an effort to develop a suppressive soil model. The analysis included the diversity and structure of the bacterial community, followed by a comparison of the relative abundance of microbial taxa between the land around healthy and infected Foc bananas. Soil samples around healthy bananas (H1 and H2) and bananas infected with Foc (I1 and I2) were taken from PTPN VIII Sukabumi land. A total of 161,259 sequences met the standard quality of the entire sample after going through the quality filtering process. H1 samples from healthy bananas showed the highest diversity value based on the alpha diversity index. The OTU obtained was dominated by the Planctomyces, Acidobacteria, and Chloroflexi groups. At the Phylum level, Actinobacteria groups are more abundant in soils around healthy bananas. Comparative analysis of abundance at the level of the family and genus shows that taxa that play a role in the cycle process include Bradyrhizobiaceae, Nitrospiraceae, Nitrospira, Rhodoplanes. Co-occurrence analysis shows a positive correlation between the relative abundance of Nitrospira and bacterial taxa that have the potential to produce compounds that are antagonistic to Foc, including Streptomyces and Kribbella. Based on the data, it can be concluded that suppressive soil conditions can be designed with an effort to increase the diversity of soil bacteria, and the abundance of bacteria in certain taxa that can be antagonistic to Foc both directly and indirectly.